Determinants of capital structure and the 2008 financial crisis: evidence from Portuguese SMEs - Proença, Pedro; Laureano, Raul M. S.; Laureano, L. (10th International Strategic Management Conference (Procedia - Social and Behavioral Sciences), 2014)
This study aims to investigate the determinants of Portuguese SMEs capital structure and to examine the effects of the 2008 financial crisis on Portuguese SMEs capital structure. The sample used considers the period 2007-2010, resulting in 12,857 Portuguese SMEs. Results suggest that liquidity, asset structure and profitability are the most important determinants explaining the capital structure of Portuguese SMEs. We report a downward tendency on companies’ debt ratios levels during the financial crisis.